Bleeding and Thrombosis: Insights into Pathophysiology of Bothrops Venom-Related Hemostasis Disorders - Sébastien Larréché (International Journal of Molecular Sciences, 2021)
Toxins from Bothrops venoms targeting hemostasis are responsible for a broad range of clinical and biological syndromes including local and systemic bleeding, incoagulability, thrombotic microangiopathy and macrothrombosis. Beyond hemostais disorders, toxins are also involved in the pathogenesis of edema and in most complications such as hypovolemia, cardiovascular collapse, acute kidney injury, myonecrosis, compartmental syndrome and superinfection. These toxins can be classified as enzymatic proteins (snake venom metalloproteinases, snake venom serine proteases, phospholipases A2 and L-amino acid oxidases) and non-enzymatic proteins (desintegrins and C-type lectin proteins). Bleeding is due to a multifocal toxicity targeting vessels, platelets and coagulation factors. Vessel damage due to the degradation of basement membrane and the subsequent disruption of endothelial cell integrity under hydrostatic pressure and tangential shear stress is primarily responsible for bleeding. Hemorrhage is promoted by thrombocytopenia, platelet hypoaggregation, consumption coagulopathy and fibrin(ogen)olysis. Onset of thrombotic microangiopathy is probably due to the switch of endothelium to a prothrombotic phenotype with overexpression of tissue factor and other pro-aggregating biomarkers in association with activation of platelets and coagulation. Thrombosis involving large-caliber vessels in B. lanceolatus envenomation remains a unique entity, which exact pathophysiology remains poorly understood.